Curcumin restrains hepatic glucose production by blocking cAMP/PKA signaling and reducing acetyl CoA accumulation in high-fat diet (HFD)-fed mice. (15th October 2018) - Wang, Zixia; Xu, Dan; She, Linlin; Zhang, Yirui; Wei, Qingli; Aa, Jiye; Wang, Guangji; Liu, Baolin; Xie, Yuan
Abstract: Objective: This study is designed to investigate whether curcumin reduces excessive hepatic glucose production (HGP) via regulation of second messenger cAMP. Methods: High-fat diet (HFD)-fed mice were orally administrated of metformin (200 mg/kg) or curcumin (50 mg/kg) daily for 10 weeks. Meanwhile, we stimulated mouse primary hepatocytes with palmitate (PA). Results: Curcumin reduced hepatic cAMP accumulation by preserving PDE4B induction, thereby suppressing gluconeogenesis via blocking cAMP/PKA activation. Curcumin reduced lipid deposition by reducing free fatty acid uptake and prevented acetyl CoA accumulation by combating mitochondrial oxidation. As a result from inhibiting acetyl CoA accumulation, curcumin protected pyruvate dehydrogenase (PDH) activity and inhibited pyruvate carboxylase (PC), limiting the shift of mitochondrial pyruvate from oxidation to gluconeogenesis via the carboxylation. Conclusion: Curcumin reduced cAMP accumulation by preserving PDE4B activity and inhibited acetyl CoA production by reducing mitochondrial fatty acid oxidation, thereby restraining pyruvate-driven hepatic glucose production. Highlights: Curcumin reduced cAMP accumulation by protecting PDE4B activity from inflammation. Preserving PDE4B activity reduced cAMP accumulation in response to glucagon response. Curcumin lowed fasting blood glucose via restraining endogenous glucose production. Curcumin reduced hepatic acetyl CoA accumulation via limiting fatty acid oxidation. Reducing hepatic acetyl CoA protected PDH activity and inhibited PC induction.